Structural Equation Model (SEM) of social capital with landowner intention - Achmad T. Nugraha; Gunawan Prayitno; Faizah A. Azizi; Nindya Sari; Izatul Ihsansi Hidayana; Aidha Auliah; Enock Siankwilimba (Economies, 2023)
The continuous loss of farmland in Indonesia is a major problem in the food production industry. The Gempol-Pandaan road, which is a section of the Trans Java toll road and connects the major cities of Surabaya and Malang, gives the Pandaan District of Indonesia its strategic location. Sustainable Food Agriculture Land (SFAL) in the Pandaan District is one strategy for expanding wetland farming. Therefore, this research aims to analyze the connection between social capital and landowners' intention to alter SFAL in Pandaan District, Pasuruan Regency, hoping to resolve existing land-use conflicts. The purpose of this study was to use partial least square structural equation modeling (PLS-SEM) to the question of how landowners' social capital is related to their intention to change land use. The PLS-SEM analysis shows that there are less opportunities for SFAL landowners to shift land use when social capital is high. Conversely, greater intentions among SFAL landowners to convert agricultural land to nonagricultural uses are associated with weaker or lower relationships among social capital characteristics.a
Keywords: 330; social capital; SEM analysis; SFAL; intention; land-use change